The effects of ESL student's Attitude on academic writing apprehensions and academic writing challenges - Akhtar, Rubina (Hampstead Psychological Associates, 2020)
The main purpose of this study is to explore the effects of ESL First year students’ attitudes on academic writing, writing apprehensions and challenges of academic writing from Universiti Teknologi Malaysia (UTM). A total number of 27 students were participated in this study. For the data collection, Writing Apprehensions Test (WAT) was developed and adapt from a test designed by (Daly & Miller, 1975). The questionnaire items were divided into three categories, first is on general students’ attitude towards academic writing, second focus on students’ academic writing apprehension and last academic writing challenges. The outcomes of this study indicate that academic challenges are the main cause for the students to be apprehensive towards writing. In addition, most importantly students’ negative attitude towards academic writing results in lack of interest towards academic writing. However, the findings show that most students are aware of the importance of ESL writing and its requirements.